(untitled) (LEARNing Landscapes, 2013)
This article advocates for the use of social networking tools as a way for teachers and students to enrich learning possibilities. While some school systems resist the use of social networking tools for learning purposes, others are moving forward with this idea. There is clearly a need for policy that will guide the decision-making and pedagogical orientations of school administrators and teachers. The authors suggest that policy surrounding the use of social networking tools such as Facebook, Twitter, and Instagram take into account two equally important objectives: innovation and safety. They propose that educational institutions create policies that empower learners to strengthen their communication skills, expand global perspectives, and create unlimited networking capacity.